Toksisitas Ekstrak Etanol Mangrove Sonneratia alba terhadap Larva Nyamuk Aedes aegypti - Usman Usman; Megawati; Munawwarah Malik; Refka Revina Melyata Ekwanda; Trini Hariyanti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Mangrove Sonneratia alba is one of mangrove species that can be found at the coast of East Borneo. Mangrove Sonneratia alba contain secondary metabolite that can be potentially as an antioxidant, antibacterial, and antifungal. The aim of this research is to know toxicity of ethanol extract of mangrove Sonneratia alba against larvae of against Ae. aegypti. The sample is mangrove Sonneratia alba obtained from Mangrove Forest Sambera of Muara Badak, East Borneo. Extraction is done by maceration method using ethanol for 3 x 24 hours. The ethanol extract obtained is then carried out phytochemical test and toxicity test method BSLT. The results showed that the ethanol extract of mangrove Sonneratia alba on the roots contain flavonoids, phenolic and triterpenoids; bark contains flavonoids, alkaloids, phenolics and triterpenoids; leaves contain flavonoids, alkaloids, phenolic, steroids and triterpenoids; and fruits contain flavonoids, alkaloids, phenolic, steroids and triterpenoids. Based on the results of toxicity testing of tissue sections of four parts mangrove extract of S. alba, has LC50 greater than 1000 ppm so that the ethanol extract of the four parts of S. alba mangrove is weak toxic.